VD_FINDINFO HC / 2011 / 535 vom 31. August 2011 - VD Tribunal cantonal (2011)
JUGEMENT DE DIVORCE, MODIFICATION DES CIRCONSTANCES, OBLIGATION D'ENTRETIEN, ENFANT | 134 al. 2 CC, 286 al. 2 CC, 308 al. 1 let. a CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)